REFORMS AND IMPROVEMENT INITIATIVES IN GOVERNMENT OF BANGLADESH: FIELD OBSERVATION AND ANALYSIS (2010-2018) - Khaled, Moslehuddin Chowdhury (American Economic & Social Review, 2024)
When it comes to improving citizen service delivery standard and processes, or broadly, management in government (MIG), many reform programs and improvement efforts are ongoing across different ministries, departments, and agencies. As part of a larger field research, this paper investigates what those programs and projects are, and how they are doing, and what the gaps are. Analyzing the publicly available data on the government portal and donors’ website, this article provides an overall idea of current reforms in various places of government. In parallel, field research was conducted through visiting agency offices, observing office environment and mechanisms, and interviewing public managers who are working at district and sub-district level offices of directorates or agencies. As a trend, state-led development process and the traditional mode of administration have moved to New Public Management based quality and performance approach. All donors have their own strategy framework document like ‘Country Assistance strategy’, ‘Country Operations and Business Plan’, Logical Framework Document, etc. Many of the projects are sectoral and agency or ministry specific, having inherent limitations, due to ‘cadre’ based organizational structural arrangement. It is common ‘not to own the projects’, rather ‘using the fund as much as possible anyway within the given project duration’. When the fund ends, implementing units or agencies leave the projects alone. That is why many projects are actually half done without significant and sustained direction.JEL Classification Codes: J18, H83, I18.